The efficacy of vapocoolant spray for the improved tolerance of catheter pain in emergency patients. (4th May 2022) - Trinder, R.; Humm, K.; Phillips, S.; Cole, L.
Abstract : Objectives: This study aimed to determine if dogs and cats presenting as an emergency had improved tolerance of intravenous catheterisation following the application of vapocoolant spray when compared to a saline control. Materials and Methods: A randomised controlled trial of client‐owned dogs and cats presenting as an emergency and requiring intravenous catheterisation was performed. Patient signalment and mentation score were recorded. All animals were restrained and had their fur clipped over the catheterisation site. They were then randomly allocated to either have a swab saturated with vapocoolant spray (treatment) or a swab saturated with saline (control) applied to the clipped area before intravenous catheterisation. The procedure was video recorded and a single blinded observer reviewed the recordings and assigned reaction scores (0 to 3) at four time points (initial restraint, limb handling, swab application and skin puncture). Results: Between October 2020 and January 2021, a total of 100 patients (79 dogs, 21 cats) were enrolled, with 50 in each group. No significant difference in species, age, breed, sex or mentation score was detected between the two groups. There was no significant difference in reaction scores between the groups at any time point with the exception of a significantly increased swab application reaction score in the treatment group compared to the control group. Clinical Significance: The indirect application of vapocoolant spray via a swab before catheterisation does not significantly reduce the reaction of dogs and cats to intravenous catheterisation in an emergency setting.